Numerical investigation of melting enhancement for paraffin in an innovative finned-plate latent heat thermal energy storage unit. (November 2021) - Wang, Hang; Xu, Hai; Liu, Changtian; Zhang, Zhen; Ling, Xiang; Jiang, Feng
Highlights: An innovative finned-plate latent heat thermal energy storage unit was proposed. Melting rate was found to enlarge with increasing fin length and fin thickness. Fin plate in direction A had a shorter melting time than that in direction B and C. Fine-tuning fin length performed much better compared to using rippling fins. Full fin configuration in direction B contributed to 46% reduction in melting time. Abstract: Latent heat thermal energy storage (LHTES) is essential for eliminating the discrepancy between energy supply and demand as well as for improving the utilization rate of low-grade industrial waste heat. This paper aims to solve the problem of long energy charge time in finned-plate LHTES device. In the present study, the LHTES unit is designed with three different orientations of the fin plates: A denotes a horizontal unit with fins; B and C denote vertical units with transverse and longitudinal fins, respectively. First, the melting process with different sizes and distributions of fins is investigated and the effect of fin thickness on the melting time is analysed. When obtaining the optimized fin parameters, two potential strengthening strategies (rippling fins and fins of non-equal length) are applied to further improve the melting performance of the device. The results show that long and thick fins can remarkably ameliorate the melting performance of paraffin, and the melting rate for the three orientations is of the order A > C > B . Compared with the finless structure, the melting rate increased by 4.52, 3.63, and 3.62 times for the three orientations of A, B, and C, respectively, for a fin length of 50 mm and fin number equal to 10. The use of rippling fins can reduce the melting time up to 4.1%, 5.4%, and 10.7% for the three orientations of A, B, and C, respectively, compared to using equal-length homogeneous fins with a thickness of 3 mm. Moreover, for orientations A and B, by adjusting fin length arrangement or using full fins, 11.4 and 46% reduction in melting time could be achieved compared with the configuration with a fin length of 50 mm and a thickness of 3 mm. The proposed innovative finned-plate LHTES device provides a useful reference and groundwork for the future large-scale utilization of the LHTES system. Graphical abstract: Image, graphical abstract